Insecticidal Activities of Ethyl Acetate Extract of Indonesian Mangrove Fungus Emericella nidulans BPPTCC 6038 on Spodoptera litura - SILVA ABRAHAM; ADI BASUKRIADI; SUYANTO PAWIROHARSONO; WELLYZAR SJAMSURIDZAL (Indonesian Society for microbiology, 2015)
Mangrove fungi are known as sources of biological active compounds. The study and the report of secondary metabolites of mangrove fungi as insecticides is very limited in Indonesia. This study assess the insecticidal activities of ethyl acetate extract of Indonesian mangrove fungus Emericella nidulans BPPTCC 6038 against Spodoptera litura (Lepidoptera, Noctuidae) neonate larvae and pupae. The fungus E. nidulans BPPTCC 6038 was isolated from leaves of mangrove Rhizophora mucronata and identified based on ITS rDNA sequence data, with the GenBank accession number KP165435, and confirmed with morphological observation. This fungus strain was grown on malt extract broth for 14 days on rotary shaker at 65 rpm, and incubated at room temperature. Mortalities of S. litura were observed on larvae fed on artificial diet containing ethyl acetate extract of E. nidulans at concentrations of 625 – 5000 ppm. The lethal concentration of the extract which causes 50% mortality of larvae (LC50 value) was 1102.27 ppm. The other effects of fungus extract on S. litura were decrease in growth rate, longer larval period, inhibition on pupal development and absence in adult emergence. The HPLC analysis of extract showed that the crude extract contained three major compounds. This study provides evidence that the extract of E. nidulans possesses insecticidal activities against S. litura.